KEMAMPUAN TEKNIK DASAR CHEST PASS BOLA BASKET PESERTA DIDIK DI SMP NEGERI 18 PONTIANAK - Hartada Hermudian; Mimi Haetami; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this research is that 80% of chest pass operands are the most frequently used in basketball compared to other types of operands. The  aims of this studyis to see the extent to which the basic technique abilities of basketball chest passes for students at SMP Negeri 18 Pontianak. The method used in this research is descriptive research method with the type of research is survey. The population in this study were all eighth grade students of SMP Negeri 18 Pontianak with a total sample of 67. Data analysis used descriptive percentages. The results of the study have different categories of 14.93% or 10 students in the excellent category, 14.93% or 10 students in the good category, 20.90% or 14 students in the moderate category, 28.36% or 19 participants students in the category of less and students who fall into the category of very less 20.90% or 14 students. Thus the results of a basic basketball chest pass technical ability test on grade VIII students in 18 Negeri SMP Pontianak. overall included in the category of inadequate, this is because there are still 49.53% or there are still half of the students who can not pass chest passes well.Keywords: bola basket, chest pass